2014
DOI: 10.3389/fpsyg.2014.00548
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating visual and auditory contributions to the cognitive restoration effect

Abstract: It has been suggested that certain real-world environments can have a restorative effect on an individual, as expressed in changes in cognitive performance and mood. Much of this research builds on Attention Restoration Theory (ART), which suggests that environments that have certain characteristics induce cognitive restoration via variations in attentional demands. Specifically, natural environments that require little top-down processing have a positive effect on cognitive performance, while city-like enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 49 publications
(102 reference statements)
3
51
3
1
Order By: Relevance
“…Cognitive Directed attention was operationalized through the construction of a composite cognitive measure, consisting of both the dual n-back (DNB) task and the BDS task. The BDS has been a common assessment of directed attention within the ART literature (e.g., Berman, Jonides, & Kaplan, 2008;Emfield & Neider, 2014); thus, the selection of BDS was largely motivated by these prior reports. DNB has not been previously administered in the context of ART, yet it was selected because it also places demands on directed attention (see Lilienthal, Tamez, Shelton, Myerson, & Hale, 2013) and shares variance with BDS (see Redick & Lindsey, 2013)ostensibly because both tasks place demands on directed attention.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive Directed attention was operationalized through the construction of a composite cognitive measure, consisting of both the dual n-back (DNB) task and the BDS task. The BDS has been a common assessment of directed attention within the ART literature (e.g., Berman, Jonides, & Kaplan, 2008;Emfield & Neider, 2014); thus, the selection of BDS was largely motivated by these prior reports. DNB has not been previously administered in the context of ART, yet it was selected because it also places demands on directed attention (see Lilienthal, Tamez, Shelton, Myerson, & Hale, 2013) and shares variance with BDS (see Redick & Lindsey, 2013)ostensibly because both tasks place demands on directed attention.…”
Section: Methodsmentioning
confidence: 99%
“…The BDS consisted of 14 trials, similar to Berman et al (2008Berman et al ( , 2012 and Emfield and Neider (2014). The task was non-adaptive, in that the digit span was not increased or decreased based on participant performance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, participants who look at a green rooftop for 40 s during the break appear to be more mentally restored than participants who look at a bare concrete roof, as found both in subjective ratings and an increase in test performance after the break (Lee et al, 2015). It should be noted though, that the restorative effects of nature exposure on subjective ratings appear to be more easily replicated than the effect on cognitive performance (Bergman et al, 2008; Emfield and Neider, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Auditory stimuli and visual stimuli, for example, can both have restorative effects even though they have different stimulus features. For instance, sound that originates from a nature source (Ratcliffe et al, 2013; Benfield et al, 2014; Emfield and Neider, 2014; Jahncke et al, 2015) has been shown to help restore mental fatigue to a greater extent than exposure to noise (e.g., ventilation noise; Alvarsson et al, 2010) and, similarly, natural sceneries are more restorative than scenes of built environments (Berto, 2005; Lee et al, 2015). Hence, stimuli with clearly different physical characteristics (pictures vs. sound) can have similar restorative effects.…”
Section: Introductionmentioning
confidence: 99%